The management of Cau Belayu Tourism Village based on green tourism business scheme - Krisna Arta Widana; I Ketut Sutama (Politeknik Negeri Bali, 2020)
Abstract Purpose: The purpose of this research is to know the implementation of green tourism business scheme by the management of the Cau Belayu tourism village to be a sustainable and environmentally friendly tourist destination. Research methods: This research is using descriptive analysis research with qualitative description. Data were collected through interviews, observations, and related documentation. The selected informants are determined based on the criteria from the author. Data were analyzed using activities that occur simultaneously, namely data reduction, data presentation, and drawing conclusions or verification. Results and discussion: The result shows that the development of tourism in Cau Belayu village is welcomed by the surrounding community because it is considered to have a positive impact on their lives and there are 10 green tourism business schemes which can be implemented in Cau Belayu tourism village to support a sustainability tourism village activities, namely compulsory, management and marketing, social involvement and communication, energy, water efficiency, purchasing, waste, travel, natural and cultural heritage, and innovation. Conclusion: The management of Cau Belayu tourism village is generally growing and developing well, but it is still not optimal because there are still several obstacles. The implementation of 10 green tourism business schemes in particular has not been fully implemented, however, the direction of the Cau Belayu tourism village management policy has led to green tourism business schemes.